The effect of dexamethasone on uterine receptivity, mediated by the ERK1/2-mTOR pathway, and the implantation window: An experimental study - Behrooz Niknafs; Naser Shokrzadeh; Mohammad Reza Alivand; Mohammad Bakhtiar Hesam Shariati (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The role of glucocorticoids in implantation has been demonstrated. Objective: This study aimed to evaluate the effect of dexamethasone on endometrial receptivity. Materials and Methods: In this experimental study, 40 BALB/c female mice aged eight wk old weighing approximately 25.0 ± 1.4 gr were used. The mice were divided into four groups (n = 10/each) of control, dexamethasone (100 μg/kg, intraperitoneal injection), mammalian target of rapamycin (mTOR) inhibitor (PP242) (30 mg/kg, intraperitoneal injection), and dexamethasone and PP242. The endometrial epithelium of the mouse was separated to measure messenger RNA expression of heart and neural crest derivatives-expressed protein 2 (HAND2), Msh homeobox 1 (Msx-1), heparin binding epidermal growth factor (HB-EGF), microRNA (miRNA) Let-7a, miRNA-145 and miRNA-451, using real-time polymerase chain reaction. Also, protein expression of mammalian mTOR and eukaryotic translation initiation factor 4E-binding protein1 (4E-BP1) was measured using western blot. Results: The results revealed that the expression of Msx-1, HAND2, HB-EGF, miRNA-451, and miRNA-Let-7a was significantly decreased in the endometrium in the dexamethasone group compared to the control, while the expression of miRNA-145 in the endometrium was up-regulated. Additionally, the administration of PP242, known as an inhibitor of mTOR, was associated with significantly reduced expression of Msx-1, HAND2, HB-EGF, miRNA-451, and miRNA-Let-7a, while PP242 induced messenger RNA expression of miRNA-145. Conclusion: It appears that dexamethasone can diminish uterine receptivity during the implantation period, at least to some extent, through the alteration of particular genes that impact endometrial receptivity. Furthermore, the mTOR pathway seemingly showed an essential role in endometrial receptivity. This article has been extracted from Ph.D. Thesis. (Mohammad Bakhtiar Hesam Shariati)